Composite material membrane for guiding tissue regeneration and preparation method thereof

By adopting a three-layer composite membrane, using collagen and acetic acid to prepare dense and loose layers, and combining hydroxypropyl methylcellulose and aliphatic polyester to prepare intermediate layers, the existing absorbable membrane has been solved at a fast degradation rate. , poor stability and poor mechanical properties have achieved better mechanical properties and tissue regeneration guidance effect.

CN119455148APending Publication Date: 2025-02-18BEIJING BONSCI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411733770.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing absorbable membranes have problems such as fast degradation speed, poor stability and easy delamination after exposure of membrane mechanical properties.

Method used

Using a composite material film composed of a dense layer, an intermediate layer and a loose layer, the dense layer and a loose layer are prepared from collagen and acetic acid, the intermediate layer is prepared from hydroxypropyl methylcellulose and aliphatic polyester, and the average pore size of the dense layer Less than the loose layer, the hydroxypropyl methylcellulose in the intermediate layer swells after contacting with acetic acid, tightly bonding to the collagen layer, and the aliphatic polyester is insoluble in acetic acid to maintain the form of the intermediate layer.

Benefits of technology

The layering problem of multi-layer films is improved, mechanical properties are improved, tissue adhesion is avoided, and the problems of the existing films are fast degradation speed, poor stability and poor mechanical properties are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455148A_ABST
    Figure CN119455148A_ABST
Patent Text Reader

Abstract

The invention provides a composite material membrane for guiding tissue regeneration and a preparation method thereof, and relates to the technical field of biomedical materials, the composite material membrane comprises a compact layer, a middle layer and a loose layer which are stacked in sequence from top to bottom; the compact layer and the loose layer are both prepared from collagen and acetic acid; the middle layer is prepared from hydroxypropyl methyl cellulose and aliphatic polyester; the average pore size of the compact layer is smaller than that of the loose layer. Hydroxypropyl methyl cellulose is swelled after being in contact with acetic acid, so that the layering problem of the multilayer film is improved; meanwhile, the aliphatic polyester is insoluble in acetic acid, so that the mechanical property of the composite material film is maintained. The compact layer plays a barrier role, and tissue adhesion is avoided. The technical problems that in the prior art, an absorbable film is high in degradation speed, poor in stability and prone to layering, and the film is poor in mechanical performance and can be rapidly broken and degraded after being exposed are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a composite material membrane for guiding tissue regeneration and a preparation method thereof. Background Art

[0002] Alveolar bone and maxillofacial bone defects are mainly caused by trauma and inflammation. Alveolar bone can be regenerated and repaired, but the regeneration rate of periodontal soft tissue is faster than that of alveolar bone, which occupies the space required for bone regeneration and makes defect regeneration difficult. Guided bone regeneration (GBR) technology is one of the most effective and reliable bone formation methods and is widely used in periodontal, alveolar and implant surgery. The ideal GBR membrane should have the following characteristics: 1. Space maintenance effect. 2. Biocompatibility. 3. Cell occlusion: prevent non-osteoblasts from invading bone defects from the mucosa. 4. Easy to operate: not too stiff, without sacrificing space maintenance function. 5. Bioactivation properties: promote wound healing and tissue integration.

[0003] The existing guided bone regeneration membranes are mainly divided into non-absorbable membranes and absorbable membranes. Common materials for non-absorbable membranes include polytetrafluoroethylene (PTFE) and expanded polytetrafluoroethylene (ePTFE) membranes, which have mechanical stability, space maintenance ability, biocompatibility and the effect of promoting bone regeneration. However, due to its high hardness, it causes soft tissue tearing, exposes the membrane, causes complications, and ultimately leads to implantation failure. And after successful implantation, a second surgery is required to remove it, and patient compliance is poor. In order to overcome the defects of non-absorbable membranes, the research trend in recent years is to develop bioabsorbable membranes. Absorbable membranes are divided into synthetic absorbable membranes and natural absorbable membranes. Synthetic absorbable membranes are mainly based on aliphatic polyesters, such as polylactic acid (PLA), poly (polyglycolic acid) (PGA) and poly (ε-caprolactone) (PCL). Synthetic polymers can precisely control the shape, thickness, porosity, mechanical strength and degradation properties of the membrane by adjusting the chemical structure and preparation conditions. Collagen membrane is the most widely used natural absorbable membrane. It has excellent biocompatibility and bioactivity, can provide a tissue regeneration microenvironment and stimulate fibroblast DNA synthesis. However, pure collagen membranes have the following disadvantages: 1. Fast degradation. 2. Poor stability and easy stratification. 3. Poor mechanical properties of the membrane, rapid fragmentation and degradation after exposure. In order to improve the durability and mechanical strength of the material, cross-linking agents have been widely studied as an effective method. The addition of chemical cross-linking agents, such as glutaraldehyde, has the advantages of low cost, high reactivity, and easy solubility in water. It is currently the most widely used traditional collagen cross-linking agent. However, studies have shown that glutaraldehyde has local cytotoxicity and induces calcification and inflammatory reactions, and is currently less used in tissue engineering.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One of the purposes of the present invention is to provide a composite material membrane for guiding tissue regeneration, so as to at least solve one of the technical problems of absorbable membranes in the prior art, namely, rapid degradation, poor stability, easy delamination, and poor mechanical properties, resulting in rapid fragmentation and degradation after exposure.

[0006] A second object of the present invention is to provide a method for preparing a composite material membrane for guiding tissue regeneration.

[0007] The third object of the present invention is to provide the use of the composite material membrane for guiding tissue regeneration or the composite material membrane for guiding tissue regeneration prepared by the above preparation method in the preparation of products for guiding or promoting tissue regeneration.

[0008] In a first aspect, the present invention provides a composite material membrane for guiding tissue regeneration, comprising a dense layer, an intermediate layer and a loose layer stacked in sequence from top to bottom;

[0009] The dense layer and the loose layer are both prepared from collagen and acetic acid;

[0010] The middle layer is prepared from hydroxypropyl methylcellulose and aliphatic polyester;

[0011] The average pore size of the dense layer is smaller than the average pore size of the loose layer.

[0012] Furthermore, the collagen is type I collagen;

[0013] Preferably, the type I collagen is extracted from animal bones, tendons or ligaments, preferably bovine Achilles tendon;

[0014] Preferably, the aliphatic polyester comprises polylactic acid, polyglycolic acid or polycaprolactone, preferably polycaprolactone.

[0015] Furthermore, the thickness of the composite material film is 0.1 to 4 mm.

[0016] Furthermore, the thickness of the dense layer is 10 to 200 μm;

[0017] The thickness of the intermediate layer is 0.03 to 1 mm;

[0018] The thickness of the loose layer is 0.2-2.5 mm.

[0019] Furthermore, the average pore size of the dense layer is 0.005 to 30 μm;

[0020] The average pore size of the loose layer is 2 to 200 μm.

[0021] In a second aspect, the present invention provides a method for preparing a composite material membrane for guiding tissue regeneration according to any one of the aforementioned embodiments, comprising the following steps:

[0022] A. Dissolving collagen in acetic acid solution to obtain a collagen solution;

[0023] B. dissolving hydroxypropyl methylcellulose and aliphatic polyester in an organic solvent to obtain an electrospinning solution, and obtaining an intermediate layer by an electrospinning method;

[0024] C. Coating a collagen solution on one side of the middle layer, freeze-drying it, and pressing it into shape to obtain a dense layer;

[0025] D. Coat the other side of the middle layer with collagen solution and freeze-dry to obtain a loose layer.

[0026] Further, the concentration of the acetic acid solution is 0.02 to 1.5 M, preferably 0.2 to 0.9 M;

[0027] Preferably, the mass concentration of collagen in the collagen solution is 0.1 to 50%, preferably 0.5 to 10%;

[0028] Preferably, the concentration of hydroxypropyl methylcellulose in the electrospinning solution is 1-20 w / v%, and the concentration of aliphatic polyester in the electrospinning solution is 5-25 w / v%;

[0029] Preferably, the organic solvent is hexafluoroisopropanol or ethanol.

[0030] Furthermore, the freeze drying comprises a first gradient freeze drying temperature of -35°C to -15°C, and a heat preservation time of 1 to 8 hours; a second gradient freeze drying temperature of -15°C to 0°C, and a heat preservation time of 10 to 40 hours; a third gradient freeze drying temperature of 10°C to 25°C, and a heat preservation time of 20 to 60 minutes;

[0031] Preferably, the pressing time is 20-70 min, and the pressing force is 0.1-2 Mpa.

[0032] Furthermore, the preparation method of the collagen comprises defatting, removing heavy metals and foreign proteins, acid dissolving, enzymolysis and purification of the crushed raw materials in sequence to obtain collagen stock solution, and freeze-drying to obtain freeze-dried collagen.

[0033] In a third aspect, the present invention provides a composite material membrane for guiding tissue regeneration as described in any one of the aforementioned embodiments or a composite material membrane for guiding tissue regeneration prepared by the preparation method as described in any one of the aforementioned embodiments in the preparation of a product for guiding or promoting tissue regeneration;

[0034] Preferably, the tissue comprises bone tissue, periodontal tissue, Achilles tendon tissue, ligament tissue, peritendon tissue, oral and maxillofacial soft tissue or oral soft tissue.

[0035] The present invention provides a composite material membrane for guiding tissue regeneration, which is composed of three layers of membranes. Since the dense layer and the loose layer are both prepared from collagen and acetic acid, the hydroxypropyl methylcellulose in the middle layer can swell in a short time after contacting the acetic acid in the dense layer and the loose layer, and dissolve in acetic acid, so that the middle layer and the collagen layer are tightly combined, improving the stratification problem of the multilayer membrane; at the same time, the aliphatic polyester is insoluble in acetic acid, which can maintain the morphology of the middle layer and maintain the mechanical properties of the composite material membrane. Since the average pore size between the dense layer and the loose layer increases from small to large, it is convenient to guide or promote tissue growth, wherein the pore size of the dense layer is smaller than that of the middle layer and the loose layer, which can isolate the growth of surrounding tissues, play a barrier role, and avoid tissue adhesion. The technical problems of the absorbable membrane in the prior art, such as fast degradation, poor stability, easy stratification, and poor mechanical properties of the membrane, rapid fragmentation and degradation after exposure, are solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is a scanning electron microscope observation image of the loose layer and the dense layer of the composite material membrane for guiding tissue regeneration provided in Example 1 of the present invention;

[0038] Figure 2 This is a scanning electron microscope observation image of the middle layer of the composite material membrane for guiding tissue regeneration provided in Example 1 of the present invention;

[0039] Figure 3 A comparison chart of the guided tissue regeneration ability test of the composite material membrane for guided tissue regeneration provided in Experiment 3 of the present invention;

[0040] Figure 4 The cytotoxicity test results of the composite material membrane for guiding tissue regeneration provided in Experiment 4 of the present invention. DETAILED DESCRIPTION

[0041] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0042] The methods and techniques of the present invention are generally performed according to conventional methods well known in the art and as described in various general and more specific references that are cited and discussed throughout the present specification unless otherwise indicated.

[0043] In one aspect, the present invention provides a composite material membrane for guiding tissue regeneration, comprising a dense layer, an intermediate layer and a loose layer stacked in sequence from top to bottom;

[0044] The dense layer and the loose layer are both prepared from collagen and acetic acid; the middle layer is prepared from hydroxypropyl methylcellulose and aliphatic polyester; and the average pore size of the dense layer is smaller than the average pore size of the loose layer.

[0045] The composite material membrane used to guide tissue regeneration is composed of three layers of membrane. Since the dense layer and the loose layer are both made of collagen and acetic acid, the hydroxypropyl methylcellulose in the middle layer can swell in a short time after contacting the acetic acid in the dense layer and the loose layer, and dissolve in acetic acid, so that the middle layer and the collagen layer are tightly combined, improving the stratification problem of the multilayer membrane; at the same time, the aliphatic polyester is insoluble in acetic acid, which can maintain the morphology of the middle layer and maintain the mechanical properties of the composite material membrane. Since the average pore size between the dense layer and the loose layer increases from small to large, it is convenient to guide or promote tissue growth, and the pore size of the dense layer is smaller than that of the middle layer and the loose layer, which can isolate the growth of surrounding tissues, play a barrier role, and avoid tissue adhesion. The technical problems of the absorbable membrane in the prior art, such as fast degradation, poor stability, easy stratification, and poor mechanical properties of the membrane, rapid fragmentation and degradation after exposure, are solved.

[0046] Type I collagen is a fibrous collagen that exists in human skin, bones, tendons and other tissues. Type I collagen is used to improve the biocompatibility of the composite film and promote cell adhesion and tissue regeneration. In some specific embodiments, the collagen is type I collagen.

[0047] Animal bones, tendons or ligaments have a high content of type I collagen and have good cell compatibility. In some specific embodiments, the type I collagen is extracted from animal bones, tendons or ligaments, preferably bovine Achilles tendon.

[0048] In some specific embodiments, the aliphatic polyester includes polylactic acid, polyglycolic acid or polycaprolactone, preferably polycaprolactone.

[0049] Among them, polylactic acid, polyglycolic acid and polycaprolactone are all absorbable materials, making the composite membrane degradable and absorbable, making it non-toxic and harmless, without causing rejection reaction, and avoiding the technical problem of requiring a second operation to remove the non-absorbable membrane in the application.

[0050] Experiments have found that the thickness of the composite material membrane not only affects the speed of guided tissue regeneration, but may also affect the growth of surrounding tissues. In some specific embodiments, the thickness of the composite material membrane is 0.1 to 4 mm.

[0051] The thickness of the composite material film may be, but is not limited to, 0.1 mm, 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm or 4 mm, and may also be any value between 0.1 and 4 mm.

[0052] Since the dense layer, the middle layer and the loose layer play a role at different stages in the process of guiding tissue regeneration, in order to enable the dense layer, the middle layer and the loose layer to play a guiding, supporting and adhering role in the process of tissue regeneration, in some specific embodiments, the thickness of the dense layer is 10 to 200 μm; the thickness of the middle layer is 0.03 to 1 mm; the thickness of the loose layer is 0.2 to 2.5 mm.

[0053] The thickness of the dense layer may be, but is not limited to, 10 μm, 30 μm, 50 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm or 200 μm, or any value between 10 and 200 μm.

[0054] The thickness of the intermediate layer may be, but is not limited to, 0.03 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm, and may be any value between 0.03 and 1 mm.

[0055] The thickness of the loose layer may be, but is not limited to, 0.2 mm, 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm, 2.2 mm or 2.5 mm, and may be any value between 0.2 and 2.5 mm μm.

[0056] The experiment found that the thickness of the dense layer, the middle layer and the loose layer not only affects the composite material membrane's guided tissue regeneration, but also has a certain impact on its mechanical strength.

[0057] The size of the pores will affect cell adhesion. During use, since the loose layer contacts the tissue to be repaired, the pores of the loose layer are larger than those of the middle layer and the dense layer. The middle layer serves as the supporting body of the composite membrane, and the dense layer serves as a barrier to the surrounding tissues, and its pore size is the smallest. In some specific embodiments, the average pore size of the dense layer is 0.005 to 30 μm; the average pore size of the loose layer is 2 to 200 μm. The average pore sizes of the dense layer and the loose layer increase from small to large, which makes a difference in the regeneration speed of tissue cells and can match the regeneration speed of tissues.

[0058] The average pore size of the dense layer may be, but is not limited to, 0.005 μm, 0.01 μm, 0.1 μm, 1 μm, 10 μm, 20 μm or 30 μm, and may also be any value between 0.005 and 30 μm.

[0059] The average pore size of the loose layer may be, but is not limited to, 2 μm, 10 μm, 30 μm, 50 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm or 200 μm, and may be any value between 2 and 200 μm.

[0060] According to another aspect of the present invention, there is also provided a method for preparing the composite material membrane for guiding tissue regeneration as described in any one of the aforementioned embodiments, comprising the following steps:

[0061] A. Dissolving collagen in acetic acid solution to obtain a collagen solution;

[0062] B. dissolving hydroxypropyl methylcellulose and aliphatic polyester in an organic solvent to obtain an electrospinning solution, and obtaining an intermediate layer by an electrospinning method;

[0063] C. Coating a collagen solution on one side of the middle layer, freeze-drying it, and pressing it into shape to obtain a dense layer;

[0064] D. Coat the other side of the middle layer with collagen solution and freeze-dry to obtain a loose layer.

[0065] The composite membrane prepared by this method has a three-layer structure, and the middle layer is prepared by electrospinning by adding hydroxypropyl methylcellulose solution to PCL solution. The loose layer and the dense layer are attached to the electrospun structure of the middle layer, which improves the overall mechanical firmness. After the hydroxypropyl methylcellulose in the middle layer contacts with acetic acid, it can swell in a short time and dissolve in acetic acid, so that the middle layer and the collagen layer are closely combined, improving the stratification problem of the multilayer membrane. However, aliphatic polyesters are insoluble in acetic acid and can maintain the electrospinning morphology, so that the prepared absorbable membrane has good mechanical properties. The loose layer uses high-purity type I collagen, which has good biocompatibility, and the freeze-dried membrane has a three-dimensional porous network structure, which can promote cell adhesion and tissue regeneration. The dense layer also uses high-purity type I collagen, but the pore size is smaller than that of the loose layer and the middle layer, which can isolate the surrounding tissue from growing in and play a barrier role.

[0066] Among them, the inner diameter of the spinneret used for spinning is 0.6mm, the spinning solution flow rate is 0.1-2mL / h, the spinning voltage is 10-26kV, the receiving distance of the flat plate receiver is 12-24cm, the drum speed is 200-800rpm, and the spinning time is 2-24h.

[0067] In some specific embodiments, the mass concentration of collagen in the collagen solution is 0.1-50%.

[0068] The mass concentration of collagen in the collagen solution may be, but is not limited to, 0.1%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, or any concentration between 0.1 and 50%, preferably 0.5 to 10%.

[0069] In some specific embodiments, the acetic acid solution is 0.02-1.5M.

[0070] The concentration of the acetic acid solution may be, but is not limited to, 0.02M, 0.05M, 0.1M, 0.2M, 0.3M, 0.4M, 0.5M, 0.6M, 0.7M, 0.8M, 0.9M, 1.0M, 1.2M or 1.5M, and may be any concentration between 0.02 and 1.5M, preferably 0.2 to 0.9M.

[0071] The acetic acid solution with a concentration of 0.2 to 0.9 M can dissolve collagen better. At the same time, the hydroxypropyl methylcellulose in the middle layer can swell when in contact with acetic acid, thereby improving the tightness with the middle layer and preventing stratification.

[0072] Since the content of hydroxypropyl methylcellulose affects the electrospinning effect of the electrospinning solution, specifically the morphology and quality of the fiber, in some specific embodiments, the concentration of hydroxypropyl methylcellulose in the electrospinning solution is 1-20 w / v%, and the concentration of aliphatic polyester in the electrospinning solution is 5-25 w / v%.

[0073] In some specific embodiments, the freeze drying includes a first gradient freeze drying temperature of -35°C to -15°C, a heat preservation time of 1 to 8 hours; a second gradient freeze drying temperature of -15°C to 0°C, a heat preservation time of 10 to 40 hours; a third gradient freeze drying temperature of 10 to 25°C, a heat preservation time of 20 to 60 minutes, so as to form three-dimensional pores with a specific pore size range.

[0074] In some specific embodiments, the pressing time is 20-70 min, and the pressing force is 0.1-2 Mpa.

[0075] In some specific embodiments, the method for preparing the hydroxypropyl methylcellulose solution comprises dissolving hydroxypropyl methylcellulose with an organic solvent under stirring;

[0076] In some specific embodiments, the method for preparing the aliphatic polyester solution comprises dissolving the aliphatic polyester with an organic solvent under stirring;

[0077] In some specific embodiments, the organic solvent is hexafluoroisopropanol or ethanol.

[0078] In some specific embodiments, the method for preparing collagen comprises defatting, removing heavy metals and foreign proteins, acid dissolving, enzymatically hydrolyzing and purifying the crushed raw materials in sequence to obtain collagen stock solution, and freeze-drying to obtain freeze-dried collagen.

[0079] The preparation method of collagen specifically comprises the following steps:

[0080] ①Pretreatment of raw materials

[0081] The raw materials were sliced ​​with a slicer to a thickness of about 1 mm, and the slices were weighed and soaked in ultrapure water at a liquid-to-mass ratio of 10:1 for a total of 72 hours, with ultrapure water replaced every 12 hours. Then, the raw materials were crushed with a meat grinder and the temperature was lowered at the same time, 1 L of pre-cooled sterile pure water was added, and after crushing, the samples were centrifuged at 5000 r / min for 10 minutes, and the precipitate was collected.

[0082] ② Degreasing treatment

[0083] Add 5% sodium carbonate solution to the precipitate, shake it for 2 hours, then replace it with a new 5% sodium carbonate solution and shake it for another 2 hours. Repeat the operation 3 times to remove fat. The purpose of defatting is to reduce the effect of fat on collagen extraction. Rinse the precipitate with pure water 5 times to wash away the sodium carbonate solution attached to the precipitate to prevent it from affecting collagen extraction, and then centrifuge and collect the precipitate.

[0084] ③Remove heavy metals and impurities

[0085] According to the liquid-to-mass ratio of 5:1, add 0.2mol / L EDTA solution with pH=10 to the precipitate, soak it at 4℃ for 24h, and change the solution every 12h to achieve the purpose of removing heavy metals and reduce the impact on collagen extraction. Then add ultrapure water to the precipitate at a liquid-to-mass ratio of 5:1, place it in a 4℃ freezer, change the ultrapure water every 15min, rinse 3 times, centrifuge and collect the precipitate. Then add 10%NaCl+0.1%Tris protein removal solution to the precipitate at a liquid-to-mass ratio of 5:1, soak it at 4℃ for 6h, and change the protein removal solution every 2h. Add ultrapure water to the precipitate at a liquid-to-mass ratio of 5:1, soak it at 4℃, change the ultrapure water every 15min, rinse 3 times, centrifuge and collect the precipitate.

[0086] ④ Acid dissolution and enzymatic hydrolysis

[0087] Add 0.5mol / L acetic acid solution to the precipitate at a liquid-to-mass ratio of 40:1, soak for 24 hours at 4°C, then add a certain amount of pepsin (1:3000) for stirring, the stirring rate is 200rpm, stir for 30 minutes every 2 hours, and enzymolysis for a period of time. Then add 30% H2O2 of 1% volume of the mixed solution to the agitator, stir for 2 hours to terminate the enzymolysis reaction. Filter the enzymolysis solution with gauze, centrifuge the enzymolysis solution with a high-speed centrifuge, collect the supernatant, obtain the collagen crude solution, and store it in a 4°C refrigerator.

[0088] ⑤ Salting out of crude collagen extract

[0089] Slowly add the evenly ground NaCl powder to the collagen crude extract while stirring until it is completely dissolved, then stop stirring and let it stand for salting out at 4°C for 24 hours. Centrifuge the salted-out collagen in a high-speed refrigerated centrifuge for 20 minutes to collect the white flocculent collagen. Use 0.5 mol / L acetic acid solution to redissolve the white flocculent collagen to the volume of the collagen crude extract before the first salting out, stir thoroughly to make the collagen fully dissolved and uniform, and perform the second salting out. Stir thoroughly to make the collagen fully dissolved and uniform, and perform the second salting out. Put the second salted-out precious flocculent collagen into a dialysis bag, dialyze it with ultrapure water at 4°C for 96 hours, replace the ultrapure water every 8 hours, and then collect the collagen in the dialysis bag to obtain the collagen stock solution, which is stored in a 4°C refrigerator.

[0090] ⑥ Freeze-dry the collagen stock solution and take a certain mass of freeze-dried collagen.

[0091] According to another aspect of the present invention, there is also provided a use of the composite material membrane for guiding tissue regeneration described in any one of the aforementioned embodiments or the composite material membrane for guiding tissue regeneration prepared by the preparation method described in any one of the aforementioned embodiments in preparing a product for guiding or promoting tissue regeneration;

[0092] In some specific embodiments, the tissue comprises bone tissue, periodontal tissue, Achilles tendon tissue, ligament tissue, peritendinous tissue, oral and maxillofacial soft tissue, or oral soft tissue.

[0093] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0094] The freeze-dried collagen used in the following examples is all made from bovine Achilles tendon as a raw material, and the freeze-dried collagen is prepared according to the collagen preparation method provided in the specification.

[0095] Example 1

[0096] A composite material membrane for guiding tissue regeneration is prepared according to the following steps:

[0097] (1) The freeze-dried collagen was re-dissolved in 0.5 M acetic acid to obtain a collagen solution with a collagen concentration of 5%.

[0098] (2) 3.6 g of hydroxypropyl methylcellulose and 9 g of PCL were mixed with 60 mL of hexafluoroisopropanol and stirred at a low speed for 24 h to obtain an electrospinning solution.

[0099] (3) Take the electrospinning solution for electrospinning. The inner diameter of the spinning needle used for spinning is 0.6 mm, the spinning solution flow rate is 1.2 mL / h, the spinning voltage is 20 kV, the receiving distance of the flat plate receiver is 18 cm, the rotation speed of the drum is 400 rpm, and it is maintained for 5 hours. The obtained electrospun membrane is placed in a vacuum drying oven at 0.8 MPa and 37°C for 12 hours for drying. The obtained electrospun membrane is used as the middle layer of the three-layer membrane, and the thickness of the middle layer is 0.2 mm for standby use.

[0100] (4) The collagen solution obtained in (2) is coated on the electrospun membrane obtained in (6), freeze-dried, and then pressed for 25 minutes with a pressing force of 1 MPa to a thickness of 0.2 mm to obtain a double-layer membrane consisting of an intermediate layer and a dense layer for standby use.

[0101] (5) The collagen solution obtained in (2) is coated on the other side of the middle layer of the double-layer membrane obtained in (7), and freeze-dried to obtain a loose layer with a thickness of 2 mm.

[0102] Among them, the freeze-drying conditions are as follows: the first gradient freeze-drying temperature is -20°C, and the insulation time is 2h; the second gradient freeze-drying temperature is -5°C, and the insulation time is 24h; the third gradient freeze-drying temperature is 24°C, and the insulation time is 30min.

[0103] That is, a composite material membrane is obtained, wherein the inner layer is a loose layer of a collagen membrane, the middle layer is a mesh film containing PCL and hydroxypropyl methylcellulose, and the outer layer is a dense layer of a collagen membrane.

[0104] Example 2

[0105] A composite material membrane for guiding tissue regeneration is prepared according to the following steps:

[0106] (1) The freeze-dried collagen was re-dissolved in 0.5 M acetic acid to obtain a collagen solution with a collagen concentration of 3%.

[0107] (2) 3 g of hydroxypropyl methylcellulose and 7.2 g of polylactic acid were mixed with 60 mL of ethanol and stirred at a low speed for 24 h to obtain an electrospinning solution.

[0108] (3) Take the electrospinning solution for electrospinning. The inner diameter of the spinneret used for spinning is 0.6 mm, the flow rate of the spinning solution is 1 mL / h, the spinning voltage is 17 kV, the receiving distance of the flat receiver is 20 cm, the speed of the drum is 300 rpm, and it is maintained for 6 hours. The obtained electrospun membrane is placed in a vacuum drying oven at 0.8 MPa and 37° C. for 12 hours for drying. The obtained electrospun membrane is used as the middle layer of the three-layer membrane, and the thickness of the middle layer is 0.2 mm, and is ready for use.

[0109] (4) The collagen solution obtained in (2) is coated on the electrospun membrane obtained in (6), freeze-dried, and then pressed for 25 minutes with a pressing force of 1 MPa to a thickness of 0.2 mm to obtain a double-layer membrane consisting of an intermediate layer and a dense layer for standby use.

[0110] (5) The collagen solution obtained in (2) is coated on the other side of the middle layer of the double-layer membrane obtained in (7), and freeze-dried to obtain a loose layer with a thickness of 2 mm.

[0111] Among them, the freeze-drying conditions are as follows: the first gradient freeze-drying temperature is -20°C, and the insulation time is 2h; the second gradient freeze-drying temperature is -5°C, and the insulation time is 24h; the third gradient freeze-drying temperature is 24, and the insulation time is 30min.

[0112] That is, a composite material membrane is obtained, wherein the inner layer is a loose layer of collagen membrane, the middle layer is a mesh film containing polylactic acid and hydroxypropyl methylcellulose, and the outer layer is a dense layer of collagen membrane.

[0113] Example 3

[0114] A composite material membrane for guiding tissue regeneration is prepared according to the following steps:

[0115] (1) The freeze-dried collagen was re-dissolved in 0.5 M acetic acid to obtain a collagen solution with a collagen concentration of 3%.

[0116] (2) 3 g of hydroxypropyl methylcellulose and 6 g of polycaprolactone were mixed with 60 mL of hexafluoroisopropanol and stirred at a low speed for 24 h to obtain an electrospinning solution.

[0117] (3) Take the electrospinning solution for electrospinning. The inner diameter of the spinneret used for spinning is 0.6 mm, the flow rate of the spinning solution is 1 mL / h, the spinning voltage is 20 kV, the receiving distance of the flat receiver is 12 cm, the speed of the drum is 500 rpm, and it is maintained for 6 hours. The obtained electrospun membrane is placed in a vacuum drying oven at 0.8 MPa and 37° C. for 12 hours for drying. The obtained electrospun membrane is used as the middle layer of the three-layer membrane, and the thickness of the middle layer is 0.2 mm, and is ready for use.

[0118] (4) The collagen solution obtained in (2) is coated on the electrospun membrane obtained in (6), freeze-dried, and then pressed for 25 minutes with a pressing force of 1 MPa to a thickness of 0.2 mm to obtain a double-layer membrane consisting of an intermediate layer and a dense layer for standby use.

[0119] (5) The collagen solution obtained in (2) is coated on the other side of the middle layer of the double-layer membrane obtained in (7), and freeze-dried to obtain a loose layer with a thickness of 2 mm.

[0120] Among them, the freeze-drying conditions are as follows: the first gradient freeze-drying temperature is -20°C, and the insulation time is 2h; the second gradient freeze-drying temperature is -5°C, and the insulation time is 24h; the third gradient freeze-drying temperature is 24°C, and the insulation time is 30min.

[0121] That is, a composite material membrane is obtained, wherein the inner layer is a loose layer of collagen membrane, the middle layer is a mesh film containing polyglycolic acid and hydroxypropyl methylcellulose, and the outer layer is a dense layer of collagen membrane.

[0122] Comparative Example 1

[0123] Compared with Example 1, no electrospun membrane was added, the collagen solution was coated on the mold, freeze-dried, and then pressed for 25 minutes with a pressing force of 1 MPa to a thickness of 0.2 mm to obtain a dense layer. The obtained dense layer was placed in a pressing mold and fixed, and the collagen solution was poured onto the surface of the dense layer, which was placed in a freeze dryer for freeze drying, and the thickness of the loose layer was 2 mm. That is, a collagen-based double-layer repair membrane was obtained.

[0124] Comparative Example 2

[0125] Compared with Example 1, the difference is that step (3) is not prepared by electrospinning, but by solvent casting, specifically according to the following operation: 2g of polycaprolactone is dispersed in 40mL of dichloromethane solution under stirring, the polycaprolactone-dichloromethane solution is poured on a glass plate, and the solvent is evaporated at room temperature. The obtained polycaprolactone film is used as the middle layer, and the thickness of the film is 0.2mm. The preparation of the dense layer and the loose layer is the same as in Example 1.

[0126] Comparative Example 3

[0127] Compared with Example 1, the difference is that hydroxypropyl methylcellulose is not added in step (2).

[0128] Comparative Example 4

[0129] Compared with Example 1, the difference is that in step (3), the electrospinning solution is taken for electrospinning, the inner diameter of the spinning needle used for spinning is 0.6 mm, the spinning solution flow rate is 0.2 mL / h, the spinning voltage is 12 kV, the receiving distance of the flat plate receiver is 18 cm, the rotation speed of the drum is 450 rpm, and it is maintained for 6 hours. The obtained electrospun membrane is used as the middle layer of the three-layer membrane, and the thickness of the middle layer is 20 μm, and it is ready for use.

[0130] Comparative Example 5

[0131] Compared with Example 1, the difference is that in step (3), the electrospinning solution is taken for electrospinning, the inner diameter of the spinning needle used for spinning is 0.6 mm, the spinning solution flow rate is 0.6 mL / h, the spinning voltage is 22 kV, the receiving distance of the flat receiver is 16 cm, the rotation speed of the drum is 600 rpm, and it is maintained for 17 hours. The obtained electrospun membrane is used as the middle layer of the three-layer membrane, and the thickness of the middle layer is 1.1 mm, and is ready for use.

[0132] Comparative Example 6

[0133] Compared with Example 1, the difference is that in step (4), the collagen solution obtained in (2) is coated on the electrospun membrane obtained in (6), and after freeze-drying, it is densely laminated to form a 5 μm film.

[0134] Comparative Example 7

[0135] Compared with Example 1, the difference is that in step (4), the collagen solution obtained in (2) is coated on the electrospun membrane obtained in (6), and after freeze-drying, the dense layer is pressed and formed to 205 μm to obtain a double-layer membrane consisting of an intermediate layer and a dense layer for standby use.

[0136] Comparative Example 8

[0137] Compared with Example 1, the difference is that in step (5), the collagen solution obtained in (2) is coated on the other side of the middle layer of the double-layer membrane obtained in (7), and freeze-dried to obtain a loose layer with a thickness of 100 μm.

[0138] Comparative Example 9

[0139] Compared with Example 1, the difference is that in step (5), the collagen solution obtained in (2) is coated on the other side of the middle layer of the double-layer membrane obtained in (7), and freeze-dried to obtain a loose layer with a thickness of 3 mm.

[0140] Experiment 1 Structure of composite membrane

[0141] The surface morphology of the composite material membrane prepared in Example 1 was observed by scanning electron microscopy. Figure 1As shown in the figure, the left picture shows the loose layer, the pores of the loose layer are 90-125 μm; the right picture shows the dense layer, the pores of the dense layer are 5-22 μm. Figure 2 As shown, the fiber diameter of the middle layer is 260-400 nm.

[0142] The structure of the composite membranes prepared in Examples 2 and 3 is similar to that in Example 1. Scanning electron microscope observation shows that the pores of the dense layer in the composite membrane prepared in Example 2 are 5 to 30 μm, the fiber diameter of the middle layer is 350 to 420 nm, and the pores of the loose layer are 110 to 150 μm. The pores of the dense layer in the composite membrane prepared in Example 3 are 2 to 20 μm, the fiber diameter of the middle layer is 300 to 500 nm, and the pores of the loose layer are 100 to 175 μm.

[0143] Test 2: Mechanical strength and anti-delamination performance test

[0144] The mechanical strength and anti-delamination performance of the composite material films of Examples 1 to 3 and Comparative Examples 1 to 9 were tested respectively.

[0145] Mechanical strength: A universal testing machine was used to cut the sample film into a size of 50 × 20 mm (length × width). In the tensile mode, a 500 N sensor was used with a loading speed of 1 mm / min and a measuring length of 5 mm.

[0146] Anti-delamination performance: It is carried out by naked eye observation. If a clear boundary line is observed between adjacent layers, it is slight delamination, if there is delamination between adjacent layers, it is delamination, and if there is no clear boundary line between adjacent layers, it is no delamination.

[0147] The specific results are shown in Table 1.

[0148] Table 1

[0149]

[0150]

[0151] As shown in Table 1, none of Examples 1 to 3 showed delamination, and the maximum breaking force was higher than that of the comparative example without delamination. Compared with Example 1, the maximum breaking force of Comparative Example 1 was reduced, and delamination occurred. The pressing method in the prior art could not improve the mechanical strength and anti-delamination performance; although Comparative Example 2 did not show delamination, its maximum breaking force was reduced, and it can be seen that the intermediate layer prepared by electrospinning can improve the mechanical strength; Comparative Example 3 did not add hydroxypropyl methylcellulose, and lacked the swelling of hydroxypropyl methylcellulose in contact with acetic acid, which resulted in delamination and reduced mechanical strength; the mechanical strength of Comparative Examples 4, 6 and 8 was reduced, and the mechanical strength of Comparative Examples 5, 7 and 9 was improved, but delamination occurred. It can be seen that the appropriate thickness of the intermediate layer, the thickness of the dense layer and the thickness of the loose layer can ensure the mechanical strength and anti-delamination performance of the composite film.

[0152] Experiment 3: Guided tissue regeneration capacity detection

[0153] In this experimental example, a rabbit dura mater defect model was constructed using New Zealand white rabbits, the composite material of Example 1 was selected as the experimental group, and the untreated rabbits were selected as the control group to test the guided tissue regeneration ability.

[0154] Corresponding specimens were taken at different time points (3 months and 6 months) for HE staining to observe tissue regeneration. Figure 3 shown.

[0155] The results showed that three months after implantation, the composite membrane provided in Example 1 was basically degraded, and the new tissue had basically replaced the composite membrane; after 6 months, the composite membrane had been completely degraded, and the autologous dura mater tissue had been completely regenerated, achieving the effect of tissue repair. Therefore, the composite membrane provided in Example 1 is suitable for preparing meningeal repair products. The results of the control group showed that there was less new tissue six months after implantation.

[0156] Test 4: Cytotoxicity, biocompatibility, etc.

[0157] Cytotoxicity: The cytotoxicity of the composite membranes of Examples 1 to 3 was tested in accordance with the provisions of GB / T 16886.5-2017. The results are as follows Figure 4 As shown, the composite membranes prepared in each example were non-cytotoxic and did not inhibit cell growth.

[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite material membrane for guiding tissue regeneration, characterized in that: It includes a dense layer, an intermediate layer and a loose layer stacked in sequence from top to bottom; The dense layer and the loose layer are both prepared from collagen and acetic acid; The middle layer is prepared from hydroxypropyl methylcellulose and aliphatic polyester; The average pore size of the dense layer is smaller than the average pore size of the loose layer.

2. The composite material membrane according to claim 1, characterized in that The collagen is type I collagen; Preferably, the type I collagen is extracted from animal bones, tendons or ligaments, preferably bovine Achilles tendon; Preferably, the aliphatic polyester comprises polylactic acid, polyglycolic acid or polycaprolactone, preferably polycaprolactone.

3. The composite material membrane according to claim 1 or 2, characterized in that: The thickness of the composite material film is 0.1-4 mm.

4. The composite material membrane according to claim 1 or 2, characterized in that: The thickness of the dense layer is 10 to 200 μm; The thickness of the intermediate layer is 0.03 to 1 mm; The thickness of the loose layer is 0.2-2.5 mm.

5. The composite material membrane according to claim 1 or 2, characterized in that: The average pore size of the dense layer is 0.005 to 30 μm; The average pore size of the loose layer is 2 to 200 μm.

6. The method for preparing a composite material membrane for guiding tissue regeneration according to any one of claims 1 to 5, characterized in that: The following steps are involved: A. Dissolving collagen in acetic acid solution to obtain a collagen solution; B. dissolving hydroxypropyl methylcellulose and aliphatic polyester in an organic solvent to obtain an electrospinning solution, and obtaining an intermediate layer by an electrospinning method; C. Coating a collagen solution on one side of the middle layer, freeze-drying it, and pressing it into shape to obtain a dense layer; D. Coat the other side of the middle layer with collagen solution and freeze-dry to obtain a loose layer.

7. The preparation method according to claim 6, characterized in that: The mass concentration of collagen in the collagen solution is 0.1 to 50%, preferably 0.5 to 10%; Preferably, the concentration of the acetic acid solution is 0.02 to 1.5 M, preferably 0.2 to 0.9 M; Preferably, the concentration of hydroxypropyl methylcellulose in the electrospinning solution is 1-20 w / v%, and the concentration of aliphatic polyester in the electrospinning solution is 5-25 w / v%; Preferably, the organic solvent is hexafluoroisopropanol or ethanol.

8. The preparation method according to claim 7, characterized in that: The freeze drying comprises a first gradient freeze drying temperature of -35°C to -15°C and a heat preservation time of 1 to 8 hours; a second gradient freeze drying temperature of -15°C to 0°C and a heat preservation time of 10 to 40 hours; a third gradient freeze drying temperature of 10°C to 25°C and a heat preservation time of 20 to 60 minutes; Preferably, the pressing time is 20-70 min, and the pressing force is 0.1-2 Mpa.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The preparation method of collagen comprises the steps of defatting, removing heavy metals and foreign proteins, acid dissolving, enzymolysis and purification of crushed raw materials to obtain collagen stock solution, and freeze-drying to obtain freeze-dried collagen.

10. Use of the composite material membrane for guiding tissue regeneration according to any one of claims 1 to 5 or the composite material membrane for guiding tissue regeneration prepared by the preparation method according to any one of claims 6 to 9 in preparing products for guiding or promoting tissue regeneration; Preferably, the tissue comprises bone tissue, periodontal tissue, Achilles tendon tissue, ligament tissue, peritendon tissue, oral and maxillofacial soft tissue or oral soft tissue.